Effects of aging on coronary flow reserve in patients with no evidence of myocardial perfusion abnormality. (25th November 2020) - Ramandika, E; Kurisu, S; Nitta, K; Hidaka, T; Utsunomiya, H; Ishibashi, K; Ikenaga, H; Fukuda, Y; Kihara, Y
Abstract: Background: Coronary flow reserve (CFR) reflects the functional capacity of microcirculation to adapt to blood demand during increased cardiac work. Purpose: We tested the hypothesis that aging had impacts on coronary flow velocities and CFR in patients with no evidence of myocardial perfusion abnormality on single photon emission computed tomography (SPECT). Methods and results: Seventy-six patients with no evidence of myocardial perfusion abnormality on SPECT undergoing transthoracic Doppler echocardiography were enrolled in this study. Patients were divided into three age groups: 17 patients aged <70 years (Group I), 38 patients aged 70–79 years (Group II), and 21 patients aged ≥80 years (Group III). Compared with Group I, CFR was significantly lower in Group II (P<0.01) and Group III (P<0.01). Multivariate analysis showed that female (P=0.03), cigarette smoking (P=0.004), hemoglobin level (P=0.001) and LV mass index (P=0.03) were determinants for resting coronary flow velocity. On the other hand, age (P=0.008), hemoglobin level (P<0.001) and LV mass index (P=0.04) were determinants for hyperemic coronary flow velocity. Age was only independent determinant for CFR (β=−0.48 P<0.001). Conclusions: Our data suggested that aging impaired CFR in patients with no evidence of myocardial perfusion abnormality primarily due to the decrease in hyperemic coronary flow velocity. Funding Acknowledgement: Type of funding source: None